IMPLEMENTASI TEKNOLOGI MIXED REALITY SEBAGAI INOVASI STRATEGI PEMBELAJARAN SISTEM PEMBANGKIT TENAGA LISTRIK ENERGI BARU TERBARUKAN - Maman Suryaman; Dian Budhi Santoso; Risma Fitriani (Bajang Institute, 2021)
Abstract: In an era that is completely digital, Information and Communication Technology (ICT) is very influential in many aspects of life, not to mention in the field of education, especially in universities. Along with the existence of an independent campus policy from the ministry of education, many universities are trying to harmonize appropriate learning methods. This can support the needs of superior human resources from higher education, so that the existence of ICT-based learning methods that present reality in a learning atmosphere is very important to design an appropriate visualization strategy. One of the ICTs that presents reality in a learning atmosphere that can be applied to the education sector is Mixed Reality (MR), which is a combination of Virtual Reality and Augmented Reality. This research will be conducted using research and development methods, where data collection will be carried out first and the selection of learning materials and end with the implementation and dissimilation. The benefits of applying this learning method are expected to create a learning environment that is closer to reality and establishes student independence in learning. The output of this research is the creation of MR-based learning materials at SMK TI Muhammadiyah Cikampek.